Inspection of the lens thickness with preoperative biometric measurements prevents an erroneous interpretation of posterior capsule during FLACS - Mei Kurosawa (Nature Portfolio, 2021)
Abstract Optical opacity reduces quality of biometry images, making it potentially difficult to find the correct location for irradiation during femtosecond laser-assisted cataract surgery (FLACS). After experiencing a case of posterior capsule (PC) rupture because of optical opacity, we started lens thickness (LT) inspection, which indicates comparison of between intra- and pre-operatively measured LT. We retrospectively investigated the effectiveness of the LT inspection. One observer reviewed all FLACS treatment summaries for 3 years by CATALYS in the Jikei University Hospital, Tokyo. Based on the lines defining the PC on intraoperative OCT images, all cases were classified into three groups: undescribed, appropriate and inappropriate PC. Among the 1070 cases, 1047 cases had appropriate PC. In 19 cases, the PC line was undescribed because of dense cataract. Among 474 cases with no inspection, 4 cases had an inappropriate PC. Whereas, in 596 cases with the LT inspection, there was no case of an inappropriate PC. LT inspection significantly reduced the cases with inappropriate PC. The safety margins normally work to prevent severe complications. However, rare outlier cases had a high risk of severe complications. We propose LT inspection could be the most practical and convenient way for safety surgery.